Binding Cellulose and Chitosan via Intermolecular Inclusion Interaction: Synthesis and Characterisation of Gel - Jiufang Duan; Chunrui Han; Liujun Liu; Jianxin Jiang; Jianzhang Li; Yiqiang Li; Chao Guan (Journal of Spectroscopy)
A novel cellulose-chitosan gel was successfully prepared in three steps: (1) ferrocene- (Fc-) cellulose with degrees of substitution (DS) of 0.5 wt% was synthesised by ferrocenecarboxylic acid and cellulose within dimethylacetamide/lithium chloride (DMAc/LiCl); (2) the β-cyclodextrin (β-CD) groups were introduced onto the chitosan chains by reacting chitosan with epichlorohydrin in dimethyl sulphoxide and a DS of 0.35 wt%; (3) thus, the cellulose-chitosan gel was obtained via an intermolecular inclusion interaction of Fc-cellulose and β-CD-chitosan in DMA/LiCl, that is, by an intermolecular inclusion interaction, between the Fc groups of cellulose and the β-CD groups on the chitosan backbone at room temperature. The successful synthesis of Fc-cellulose and β-CD-chitosan was characterised by 13C-NMR spectroscopy. The gel based on β-CD-chitosan and Fc-cellulose was formed under mild conditions which can engender autonomous healing between cut surfaces after 24 hours: the gel cannot self-heal while the cut surfaces were coated with a solution of a competitive guest (adamantane acid). The cellulose-chitosan complex made by this method underwent self-healing. Therefore, this study provided a novel method of expanding the application of chitosan by binding it with another polymer.